Complex speech act as a performance of fallacies in Nouri al-Maliki’s political speeches - Hamad, Saad Saleh; Afida Mohamad Ali,; Shamala Paramasivam,; Mohd Azidan Abdul Jabar, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Pragmatics has revealed how the discourse of political speakers contains deliberate persuasive and manipulative claims which are carried out by an array of speech acts. Most of the time, such claims can be questionable as the meaning of a claim cannot be arrived at without considering additional elements, including the function of the speech act and the context of the utterances under investigation. Previous studies on speech acts were conducted to interpret the illocutionary act of a single utterance; no study has addressed the act of a series of utterances. Therefore, it is necessary to interpret the illocutionary act of a series of utterances that can be employed for a particular purpose as the real intention might not be expressed within a sentence. Hence, this study focusses on the notion of fallacies which refer to faulty arguments that consist of more than one utterance, and together they comprise a series of speech acts. Such a chain of speech acts needs to be interpreted precisely to uncover the illocutionary force of such complexity. This study followed a textual analysis method and adopted Van Eemeren, Grootendorst, and Henkemans (2002) pragma-dialectical approach to analyze the speech act of fallacies in ten political speeches of Prime Minister Nouri al-Maliki. The study found that the illocutionary force at the sentence level is different from the illocutionary force at the argumentation level. The study concluded that within political discourse, fallacies need to be analyzed as a complex speech act; otherwise, analyzing fallacies as a single act may result in an insufficient interpretation as the illocutionary force of fallacies does not exclusively rely on the properties of the verbal form of fallacies, rather, it depends on the function of such properties in the context and the concerned situation.